Epidemiology of patellar tendon injury in elite male soccer players. Issue 4 (27th March 2011) - Hägglund, M; Waldén, M; Zwerver, J; Ekstrand, J
Abstract : Background: Patellar tendon injuries are common in jumping sports. The epidemiology in soccer is not well described. Objective: To study the epidemiology of patellar tendon injury in elite male soccer players and evaluate potential risk factors. Design: Prospective cohort study. Setting: Men's professional soccer. Participants: 51 European elite soccer clubs (2229 players) from three different cohorts; Swedish First League and Union of European Football Associations (UEFA) Champions League cohorts playing at home grounds with natural grass, and UEFA Artificial Turf cohort playing on third generation artificial turfs, were followed between 2001 and 2009 over a varying number of seasons. Assessment of risk factors: Internal (age, stature, body mass) and external (total exposure, training/match exposure ratio, team home surface, seasonal distribution, playing position) risk factors were investigated using multivariate logistic regression. Main outcome measurements: Patellar tendon injury (insidious onset tendinopathy or acute partial rupture) leading to time-loss from soccer. Results: 139 patellar tendon injuries were recorded (1.5% of all injuries) with an incidence of 0.12 injuries/1000 h and a season prevalence of 2.4%. Most injuries (60%) were minimal to mild (<8 days absence), and 19% were recurrent complaints. No difference in season prevalence (OR 0.96, 95% CI 0.62 to 1.48) or incidence (RR 1.22, 95% CI 0.84 to 1.77) was observed between teams playing on artificial turf and natural grass. Multivariate logistic regression showed that high total exposure hours (OR 1.02 per 10 h increase; 95% CI 1.00 to 1.04) and increased body mass (OR 1.16 per 5 kg increase; 95% CI 1.00 to 1.34) were significant risk factors for patellar tendon injury. Conclusion: Although mainly mild in nature, patellar tendon injuries are fairly common in elite soccer and the recurrence rate is high. Exposure to artificial turf did not increase the risk of injury. Increased body mass and high total amount of exposure were identified as risk factors for patellar tendon injury.